PUTUSNYA PERKAWINAN (PERBANDINGAN MAZHAB FIQH) - Attahiraa Prajna Paramitha; Diella Anggieta Maharani (El 'Ailaah, 2026)
Marriage in Islam holds a sacred meaning as a form of a holy covenant between a man and a woman to build a harmonious family. However, marriage can be dissolved due to death, divorce, or a court ruling. This study aims to explain the concept of marriage dissolution in the perspectives of various fiqh schools of thought and to compare their views. The research method used is normative legal research with a library research approach. This study examines the views of the four major schools of thought Hanafiyah, Malikiyah, Syafi’iyah, and Hanbali regarding the forms of marriage dissolution, such as talak, fasakh, khulu’, ila’, syiqaq, li’an, zhihar, and taklik talak. The results of the study show that there are differences in the schools' views regarding the laws, procedures, and reasons that justify marriage dissolution. Talak, for instance, is classified into several types according to the stipulations of each school. Meanwhile, fasakh and khulu’ also have specific mechanisms in each school of thought. By understanding these differences, this study provides an in-depth insight into the flexibility and dynamics of Islamic law in resolving marital issues.